Hygroscopic growth of CsI and CsOH particles in context of nuclear reactor accident research. (June 2019) - Mishra, Gaurav; Mandariya, Anil Kumar; Tripathi, S.N.; Mariam,; Joshi, Manish; Khan, Arshad; Sapra, B.K.
Abstract: Studies of behavioral characteristics of fission product aerosols are extremely important in context of suspected environmental release during a severe nuclear reactor accident. Fission product aerosols generated in such a case are expected to travel from coolant systems to the containment and may get released to the environment in the most unlikely scenario of containment breach. Presence of steam also affects their dynamic behaviour and fate. Interaction of aerosol particles with water vapor in subsaturation domain modifies their physical and chemical characteristics. The objective of this study was to examine the hygroscopic nature of nuclear accident relevant cesium bound compounds viz. CsI, CsOH with the use of Hygroscopic Tandem Differential Mobility Analyzer (HTDMA). The growth factors for single component aerosols were obtained for different initial size of particles at different relative humidity levels. Growth factor curves as well as deliquescent parameters for CsI and CsOH particles have been obtained for the first time and have a crucial role towards environmental source term estimations in the event of nuclear accident. Experimental results were also compared with the theories available in literature. Highlights: The hygroscopic nature of nuclear reactor accident relevant cesium bound compounds viz. CsI, CsOH has been studied. First time determination of DRH and ERH of CsI particles. The experimental results have been compared with the available theoretical models of hygroscopic growth.